Review of recycling alternatives for paper pulp wastes - Vilarinho, Inês Silveirinha; Gameiro, Tânia; Capela, Marinélia N.; Carvalheiras, João; Caetano, Ana P. F.; Novo, Catarina; Novais, Rui M.; Seabra, Maria Paula; Labrincha, João António (Frontiers in Materials, 2022)
The demand for products derived from the pulp and paper industry has been increasing over the past years and is projected to further increase over the coming decades. Although being one of Portugal’s most relevant industrial activities, contributing to nearly 2.3% of the GDP, this sector is known to generate a variety of wastes including fly ashes, exhausted bed sands, green liquor dregs, grits, lime muds, biological and pulp and paper mill sludges, which have been mostly disposed of in landfills. This strategy is not aligned with the circular economy vision, and therefore it is imperative to develop new recycling routes for the different waste streams. This scenario has driven a significant research effort in the attempt to design sustainable recycling alternatives for the distinct wastes. This study summarizes the investigations focusing on the valorisation of these wastes in a wide range of applications, including the production of low carbon footprint binders or mortars for the construction sector, but also the production of novel materials for high added-value applications such as wastewater treatment and pH regulation. The present work also highlights the main bottlenecks and future prospects for the studied wastes.